2016
DOI: 10.1186/s12870-016-0790-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression profiling reveals a role of the root apoplast in local phosphate response

Abstract: BackgroundPlant adaptation to limited phosphate availability comprises a wide range of responses to conserve and remobilize internal phosphate sources and to enhance phosphate acquisition. Vigorous restructuring of root system architecture provides a developmental strategy for topsoil exploration and phosphate scavenging. Changes in external phosphate availability are locally sensed at root tips and adjust root growth by modulating cell expansion and cell division. The functionally interacting Arabidopsis gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 91 publications
(131 reference statements)
7
76
1
Order By: Relevance
“…Transcriptomic analysis of Pideprived stop1 and almt1 seedlings showed that malate treatment reactivates the low-Pi responsiveness of genes that encode extracellular proteins involved in cell-wall modification and ROS homeostasis, such as peroxidases (34). Our transcriptomic results confirm a previously reported role of apoplastic peroxidases in the Pi-starvation response (33), and highlight the role of malate secretion in the cell-wall remodeling processes potentially involved in the changes of Arabidopsis root system architecture induced by low Pi availability. In this context, the finding that UPBEAT1, a transcription factor that modulates the transition from cell proliferation to cell differentiation in the RAM by repressing peroxidase genes (37), is repressed in response to Pideficiency conditions and the fact its expression is altered in stop1 and almt1, support the notion that ROS generation plays an important role in the root response to Pi deprivation.…”
Section: Malate Treatment Rescued the Expression Of Local-response Genessupporting
confidence: 79%
See 3 more Smart Citations
“…Transcriptomic analysis of Pideprived stop1 and almt1 seedlings showed that malate treatment reactivates the low-Pi responsiveness of genes that encode extracellular proteins involved in cell-wall modification and ROS homeostasis, such as peroxidases (34). Our transcriptomic results confirm a previously reported role of apoplastic peroxidases in the Pi-starvation response (33), and highlight the role of malate secretion in the cell-wall remodeling processes potentially involved in the changes of Arabidopsis root system architecture induced by low Pi availability. In this context, the finding that UPBEAT1, a transcription factor that modulates the transition from cell proliferation to cell differentiation in the RAM by repressing peroxidase genes (37), is repressed in response to Pideficiency conditions and the fact its expression is altered in stop1 and almt1, support the notion that ROS generation plays an important role in the root response to Pi deprivation.…”
Section: Malate Treatment Rescued the Expression Of Local-response Genessupporting
confidence: 79%
“…Interestingly, using SUBA, a subcellular prediction tool (35), we found that 30% of proteins encoded by genes whose responsiveness to low Pi is restored by malate treatment in stop1 and almt1 Pi-deprived seedlings are targeted to the apoplast or extracellular region (Fig. 6B), confirming a previous study in which a major role of the apoplast in the root response to Pi starvation was highlighted (33). Furthermore, an additional 16% of genes are targeted to the plasma membrane (Fig.…”
Section: Malate Treatment Rescued the Expression Of Local-response Genessupporting
confidence: 70%
See 2 more Smart Citations
“…In Pi-deficient plants, iron acquisition genes are generally down-regulated to compensate for increased iron levels (Misson et al, 2005;Lan et al, 2012). Down-regulation of iron acquisition genes is a consequence of oxidatively precipitated iron, which is deposited in the meristematic and elongation zones of the root as a prerequisite of Pi deficiency-induced determinacy of primary root growth (Müller et al, 2015;Hoehenwarter et al, 2016, Mora-Macías et al, 2017. While a molecular function has yet to be assigned to the two IRPs, bHLH39 was shown to form a heterodimer with the master regulator of iron homeostasis FIT (bHLH29), which controls the expression of a large subset of genes involved in the acquisition and homeostatic control of iron (Colangelo and Guerinot, 2004;Jakoby et al, 2004;Yuan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%